2022
DOI: 10.33448/rsd-v11i3.26715
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils of Lippia gracilis and Lippia sidoides chemotypes and their major compounds carvacrol and thymol: nanoemulsions and antifungal activity against Lasiodiplodia theobromae

Abstract: The aim of this work was to evaluate the antifungal activity of essential oils (EOs) of Lippia gracilis and Lippia sidoides accessions, their major compounds and nanoemulsions. Nanoemulsions with 18% of EO or major compound were produced by spontaneous emulsification method. The EO of two L. gracilis accessions (LGRA-106 and LGRA-109) and two L. sidoides accessions (LSID-102 and LSID-104) were extracted by hydrodistillation and the major compounds thymol and carvacrol were purchased commercially. Antifungal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Essential oils from various host plants have been tested against several plant pathogens because plant-derived essential oils exhibit environmentally friendly control characteristics [ 17 , 18 , 20 , 35 ]. In a previous study, Rasooli et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils from various host plants have been tested against several plant pathogens because plant-derived essential oils exhibit environmentally friendly control characteristics [ 17 , 18 , 20 , 35 ]. In a previous study, Rasooli et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, De Melo et al. [ 35 ] reported that essential oils of Lippia gracilis and Lippia sidoides exhibited significant, antifungal activity against Lasiodiplodia theobromae , the causal fungus of diplodia pod rot of cocoa.…”
Section: Discussionmentioning
confidence: 99%
“…Separations were performed on a Rtx ® -5MS Restek (5%-diphenyl-95%-dimethylpolysiloxane) fused silica capillary column (30 m x 0.25 mm i.d. x 0.25 µm film thickness), Helium as carrier gas at a constant flow of 1.0 mL min -1 [17].…”
Section: Extraction Of Essential Oils (Eo) and Analysis Of Chemical C...mentioning
confidence: 99%
“…Molecules in the GC/MS were ionized by electron ionization at 70 eV. Fragments were analyzed by a quadrupole system programmed to filter fragments/ions at m/z from 40 to 500 Da and detected by an electron multiplier [17].…”
Section: Extraction Of Essential Oils (Eo) and Analysis Of Chemical C...mentioning
confidence: 99%
“…Suas folhas e flores formam a fração medicinal desta planta. Utilizado de diferentes formas e contendo até 4,5% de óleo essencial (OE) abundante em timol e carvacrol, o alecrim-pimenta apresenta fortíssima atividade antimicrobiana e antifúngica (Matos;Lorenzi, 2008;Monteiro et al, 2020;Melo et al, 2022).…”
Section: Introductionunclassified